3(x-7)-15=-3

Simple and best practice solution for 3(x-7)-15=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-7)-15=-3 equation:



3(x-7)-15=-3
We move all terms to the left:
3(x-7)-15-(-3)=0
We add all the numbers together, and all the variables
3(x-7)-12=0
We multiply parentheses
3x-21-12=0
We add all the numbers together, and all the variables
3x-33=0
We move all terms containing x to the left, all other terms to the right
3x=33
x=33/3
x=11

See similar equations:

| 7–2(8n-3)=4(n−2)22 | | 1/3(3x27)=1 | | 1/2(3x+2)=5 | | 1-5x=24 | | –2f+8=–f | | 1+x+5=11+4x | | -6+m/4=-11 | | 3=-1-5+9a | | 6j+9=-9 | | 7x-4(x+2)=-85 | | 15=4x1 | | 6–t=2t | | -4+3+2x=89 | | 4+1/3=n6 | | -9k+1=-8k+10 | | 3(x+9)=-3(4x-5)+6x | | 4x-30=7(-2x+2+10 | | 2x-4=3x=6 | | 9-b=11 | | 3(x-2)=(6x-12)÷3 | | 6|4y-8=-2 | | a+7/3=-3 | | −6x−16=2x | | 8h=8+10h | | 28+21m-14=35+14-14m | | 7x-2+1=5x+7 | | 3x+2=-x+34 | | 7(2n-3)=119 | | 28+21m-14=35+14-24m | | -5(9+y)=20-3+6y | | (3x)=(2x)+65 | | -4+4x=90 |

Equations solver categories